Suitability evaluation of rural tourism based on AHP and fuzzy evaluation method. Issue 3 (May 2019) - Xing, Yunheng; Li, Sheng; Liao, Jianjun; Wang, Zhiyuan; Wu, Bo
Abstract: In order to study the suitability of rural tourism development and prevent the blind development of rural tourism, we have identified 12 evaluation indicators of natural resources and human resources from three aspects: tourism resources, current development intensity and village development potential. Using AHP and fuzzy evaluation method to quantitatively analyze the various elements of rural tourism development, and evaluate the suitability of village development tourism industry.